Focusing on the value of cooperative learning in physical education: a bibliometric analysis - Zhou, Tong; Wang, Huayi; Li, Dong (Frontiers in Psychology, 2023)
The shift towards cooperative learning has highlighted the growing advantages of individual learning modes during the transition. Nevertheless, a systematic compilation of the precise classification and developmental dynamics of cooperative learning in PE has been absent. This study aimed to organize the existing progress and significance of collaborative learning. The study entailed a meticulous systematic review process, examining 169 articles in this domain with the aid of visualization software. The results of the study indicate that the overall use of cooperative learning in physical education is on the rise and will reach its highest level in 2021; Second, the keywords, major core scholars, journals, countries, and major research topics..; the visual knowledge map reveals the major research topics of intrinsic motivation, cooperative learning, motor skills, self-learning, written expression, and pedagogical models.The research primarily centers on primary and secondary education, followed by teacher training and higher education. At the primary and secondary school levels, there is a specific focus on aspects such as motivation, teacher-student relationships, and the group atmosphere. This research also explores sustainable development and training for PE teachers, model integration, and its influence on students' intrinsic motivation; and finally, the future directions of cooperative learning in PEare summarized. This study provides meaningful and valuable information on how cooperative learning models can be used and developed in various teaching and learning environments, physical education teacher education, and overall student development.